Associations between level of private dental insurance cover and favourable dental visiting by household income. (December 2015) - Teusner, DN; Brennan, DS; Spencer, AJ
Abstract: Background: The aim of this study was to assess associations between level of dental insurance cover and dental visiting across socioeconomic groups in an Australian population. Methods: Data were sourced from the 2008 National Dental Telephone Interview Survey and a related mailed survey. Analysis included dentate adults (≥18 years) (n = 1984) with known dental insurance status (categorized as no cover, lower and higher level cover). Adjusted prevalence ratios (PR) of a favourable visiting pattern (FVP) were estimated stratified by household income group. Results: Mailed survey response was 68%. Overall 38.3% had a FVP. Compared to uninsured adults, adjusted PR of FVP were significantly higher for insured adults with lower or higher level cover. However, among insured adults, there was no significant difference in FVP by level of cover. Among adults in the lowest income group, both lower (PR = 2.32, 95% CIs: 1.74, 3.08) and higher cover groups (PR = 2.34, 95% CIs: 1.60, 3.40) had higher prevalence of FVP than uninsured adults. For the highest income group there was no significant difference in FVP between the uninsured and insured groups. Conclusions: While the level of cover was not associated with dental visiting, findings indicated that insurance may improve access and orientation of dental care for lower socioeconomic adults but have less influence on access patterns of higher socioeconomic adults.